(untitled) (Medico Legal Update, 2020)
The aim was to see the effect of wedge sea hare extract and papaya juice, on Hemoglobin and Ferritin levels of Mice Strain (BALB / c). Method, True Design Experiment with Control Group, has been used. Mice were divided into 5 groups, each group 5 tails, reserves 5 tails. Intervention of mice was given a solution of collaborative compounds (a mixture of sea rabbit extract with papaya juice) for 21 days, with the distribution of the following doses: Group A, Control (-), Group B, Control (+), Fe tablets 0.65 mg / kg BW, Group C, dose treatment = 100 mg / kg BW of mice / day, Group D, dose treatment = 150 mg / kg BW of mice / day, Group E, dose treatment = 250 mg / kg BW mice / day. Blood is taken before and after treatment 21 days. Data Analysis using a Paired t-test and ANOVA statistical tests. The results, statistical tests showed a significant difference in hemoglobin levels that were significant in the three treatments, between before and after treatment, with P <0.05. This means that the administration of wedge sea hare extract and papaya juice can increase Hemoglobin levels in anemia mice, where there is a tendency to increase the average hemoglobin level along with the large dose of treatment given. Besides, it is also due to the presence of primer metabolic substances in papaya juice, such as vitamin C, Beta carotene, Calcium, Potassium, and Phosphorus. Conclusion, there is a different increase in hemoglobin levels in the three forms of treatment between before and after treatment. This means that there is a significant effect of giving collaborative compounds to Hemoglobin levels in mice.